The Problem of Securalism - Asep Awaludin; Kusuma Dewi Nur Aini (Journal of Comparative Study of Religions (JCSR), 2021)
This paper attempts to discuss the discourse related to secularism. Secularismis an ideology that is understood as a process of separation between religion and theworld. The existence of this ideology can eliminate (nihilism) the traditional value ofthe concept of God in human life. When examined more deeply, history appears thatsecularism can cause several problems that affect the confusion in human life. This canbe seen from the social, economic and political fields. First, in social life, it gives riseto a social theory related to social life, namely Marxism, a theory that teaches humanawareness how to socialize which affects a very materialist economic attitude. Thesecond is in the economic field, so that in the process it gives rise to capitalism, whichis one of the incarnations of secularization in the economy. Third, in politics there is aseparation between religion and state. From this impact affects human life. The role ofWestern thinkers has also influenced the emergence of secularism in human life. Withthe development of secularism in people’s lives, it also affects religious attitudes inlife. In this study, secularism greatly affects people’s life, especially in modern timeslike today. So that we need a theory based on Islam to criticize this problem. The roleof Western thinkers has also influenced the emergence of secularism in human life.With the development of secularism in people’s lives, it also affects religious attitudein life. In this study, secularism greatly affects people’s life, especially in modern timeslike today. So that we need a theory based on Islam to criticize this problem. The roleof Western thinkers has also influenced the emergence of secularism in human life.With the development of secularism in people’s lives, it also affects religious attitude